Advance in clinical application of Traditional Chinese Medicine collapse therapy in the treatment of hemiplegia after stroke (中药塌渍治疗中风偏瘫的临床应用进展) - ZHANG Nannan (张楠楠); TUO Yuhong (庹玉红); GENG Qingwen (耿庆文); HE Xuelian (何雪莲); LIU LI (刘丽) (Association of Integrative Nursing, 2021)
This paper introduced the current status of clinical application of Traditional Chinese Medicine (TCM) collapse therapy in the treatment of hemiplegia after stroke, and summarized the advance of TCM collapse therapy and its clinical application with other TCM techniques. The TCM prescription adopted in collapse therapy remains controversial, and more efforts should be paid to clarify the standard operating procedure of collapse therapy. (本文介绍了中药塌渍治疗中风偏瘫的临床应用现状, 总结了中药塌渍联合技术治疗进展, 虽然中药塌渍治疗中风偏瘫效果明显, 但对中药处方的应用尚存在争议, 技术操作规范有待进一步明确。)